(untitled) (Research, Society and Development, 2023)
With the spread of SARS-CoV-2, a type of aerosol-spread coronavirus that initially spread in China in 2019, a public health emergency has been declared by the World Health Organization. It is a virus with a high propagation capacity, so it is necessary to use biosafety measures during dental practice in the dental office, which is an environment with a high concentration of aerosols. Therefore, the current work aims to analyze the biosafety crisis in the pre-pandemic context and its impact in the post-pandemic context, so that there is a reduction in the risk of virus infection, thus protecting patients and dental professionals. For this study, an integrative literature review was conducted through recent biosafety manuals, the means of search used were Google Academic, SciELO, Capes journal portal and PMC (PubMed Central), in the period 2022. Between the years 2016 to 2022, 1030 articles related to the topic were identified, then, 42 articles that met the inclusion criteria were adopted. Adopting new standards of individual protection - especially regarding the use of masks such as N95 and PFF2 -, of cleaning surfaces, and of care protocols was of notable relevance to prevent contagion, since the combination of these acts proved effective in protecting patients and dental professionals, compared to the old customs. Therefore, it was found that analyzing new biosafety methods is essential to avoid infection and provide a safer environment for patients, staff, and dental surgeons.